Transcriptomic and proteomic signatures of host NK cells delineate distinct immune states across tuberculosis infection statuses - Han Zhang; Liguo Liu; Jie Hu; Xiaolin Wu; Jianhua Zheng; Henan Xin; Jiang Du; Jiarong Yang; Zizheng Lv; Zhuoran Wu; Lei Gao; Rongmei Liu; et al. (Frontiers in Immunology)
IntroductionAlthough natural killer (NK) cells play crucial roles in the immune response to Mycobacterium tuberculosis (M.tb) infection, systematic investigations delineating the immune characteristics of NK cells across the tuberculosis (TB) disease spectrum are scarce.MethodsThis multiomics study employed transcriptomic, proteomic, and RT-qPCR analyses to characterize and validate CD56+ NK cells from 165 participants stratified by TB infection status (active TB (ATB), latent TB infection (LTBI), and healthy control (HC)). Peripheral blood samples from an independent cohort of 85 participants were subjected to flow cytometry analysis and validation.Results and discussionEnrichment analyses of transcriptomic and proteomic data revealed that the NK cell-mediated cytotoxicity and apoptosis pathways were enriched in LTBI and ATB groups, whereas chemotaxis-related pathway enrichment was specific to ATB. Further analysis revealed that the expression of genes mediating the NK cell-mediated cytotoxicity signaling pathway through perforin–granzyme was upregulated in the LTBI state, whereas that of those associated with death receptors was elevated in ATB, potentially indicating a transformation of NK cell function in different TB infection states. Moreover, analysis of ATB-specific chemotaxis genes suggested that the migration of NK cells was likely to occur in the ATB state. Flow cytometry revealed an increased frequency of CD56dim NK cells and a decreased frequency of CD56bright NK cells in individuals with LTBI versus that in HCs in an independent cohort. In addition, RT-qPCR validation identified a four-biomarker combination (SLC7A5, PDE4D, CXCR4, and SOCS3) distinguishing ATB from HCs, a three-biomarker combination (SLC7A5, PER1, and PDE4D) differentiating LTBI from HC, and a three-biomarker combination (SOCS3, GZMK, and HIST1H3B) differentiating ATB from LTBI. These findings elucidate the immune clearance mechanism of NK cells in TB and provide clinically actionable biomarkers for infection staging, advancing our understanding of TB immunopathogenesis.